Islamisasi Dan Pertumbuhan Institusi-Institusi Pendidikan Islam Di Nusantara - Izzi Fekrat; Duski Samad; Elda Rifai (STIKes Ibnu Sina Ajibarang, 2024)
This article outlines the importance of Islamic education in guiding individuals towards righteousness and substantial meaning. Islamic education plays a key role in developing the physical, spiritual, and intellectual aspects of individuals integratively. The history of Islamic education in Indonesia aligns with the process of Islamization in the archipelago, starting with the initial steps of Muslim converts to deeply study religious teachings. From traditional learning in homes, small mosques, and larger mosques, to the development of systematic education in the form of Islamic boarding schools (pondok pesantren) and madrasas. This article highlights the process of Islamization and the growth of Islamic educational institutions in the archipelago as the main focus of research. The research method employs a qualitative approach drawn from various sources, articles, and journals.